Resolution Of The Main Character's Inner Conflict In The Novel Sunset & Rosie By Tere Liye (Wolfgang Kohler's Theory) - Khoirun Nisa; Qurrotul A’yuni (Penerbit Hellow Pustaka, 2024)
The problem discussed in this research is conflict and its resolution in the novel Sunset & Rosie by Tere Liye. This research aims to describe the conflict and problem solving (resolution) contained in the novel Sunset & Rosie by Tere Liye. The theory used is Wolfgang Kohler's which discusses a deep understanding (insight) that creates problem solving (resolution). This aims to find out how the characters behave in dealing with the conflict that occurs. The method used in this research is descriptive qualitative, namely a method intended to create systematic, factual and accurate descriptions, images or paintings regarding the facts, characteristics and relationships between the phenomena being investigated. The data source in this research is the novel Sunset & Rosie by Tere Liye. The research results illustrate that in the novel Sunse & Rosie by Tere Liye there are several inner conflicts and their resolutions, namely, two individual conflicts with themselves and five individual conflicts with other individuals. Conflict resolution is found using several efforts including tolerance, negotiation or offers, taking concrete action, providing promises or guarantees and so on.